MEDIA PEMBELAJARAN BAHASA BERBASIS SAMPAH ORGANIK SEBAGAI PENGENALAN ECOLITERACY SISWA SEKOLAH DASAR - Azmussya'ni, Azmussya'ni; MZ, Dedy Sofian (Universitas Hamzanwadi, 2022)
The purpose of this study was to develop language learning media based on organic waste as an introduction to ecoliteracy for elementary school. This study uses a development research method that refers to the Borg and Gall development model. Data collection methods in this study were questionnaires and observations. Data analysis in this research is descriptive quantitative with categorization technique. Based on the results of the study, it showed that the final product of learning media development based on organic waste at SDN 3 Kabar after going through a series of development procedures, was feasible to be implemented. Based on the results of product trials that have been carried out, there are significant changes between the pretest and posttest on students' understanding of Ecoliteracy. The indicator “merasa dini bagian dari alam” when the pretest percentage of students who are able to understand is 29.6% and when the posttest is 63.0%. The percentage of indicator “mampu mendeskripsikan pengertian dan jenis sampah” from 14.8% become 63.0%. The last indicator is ”mampu mendeskripsikan dampak negative sampah” from a percentage of 0% increasing to 29.6%. This shows that the introduction of ecoliteracy through developing language learning media based on organic waste to students at SDN 3 Kabar was successful.Keyword: Language Learning Media Development, Organic Waste, Ecoliteracy